Peru potato potential: Biodiversity conservation and value chain development. Issue 1 (26th July 2016) - Tobin, Daniel; Bates, Rick; Brennan, Mark; Gill, Tom
Abstract: Although crop diversity has been identified as essential to enhance global food security and adapt to climate change, high loss of genetic resources is occurring due to agricultural industrialization and market requirements. Value chain development is an emerging market strategy that seeks to simultaneously achieve agrobiodiversity conservation and economic goals, though little empirical evidence exists regarding the extent to which value chains encourage biodiversity maintenance. This study considers the conservation of native potatoes among households in the highlands of Peru where value chain development is being pursued to create market niches for certain native potato varieties. Utilizing a mixed-methods case study approach, the findings of this study indicate that the conservers of native varieties are the households with more endowed resource bases as well as those that sell native varieties in value chains. However, the findings suggest that value chains themselves likely have only a marginal effect on conservation. Native potato conservation and potato production for value chains exist as two separate livelihood activities, and households with more resources are best positioned to engage in both. While value chains allow households to capitalize on the economic value of certain native varieties, the production of other native varieties allows households to fulfill cultural values. Based on these findings, this study concludes that value chain opportunities for native varieties should continue to be identified but they alone are not an adequate strategy to conserve agrobiodiversity. Therefore, in addition to value chain development, a full suite of conservation schemes should be implemented simultaneously.